Ice drift during the 1897 Andrée balloon expedition - Lantz, Björn (Polar Record, 2019)
The indirect cause of death of the three members of the Andrée balloon expedition on White Island in early October 1897 was the ice drift during their attempted retreat after the forced landing at 82°56'N 29°52'E. They initially tried to reach Cape Flora to the southeast of their current position in the Arctic pack ice even though they could deduce from prior explorers’ experience that the expected long-term direction of the ice drift in the area would be to the southwest. However, when they finally turned towards the Seven Islands in the southwest, the ice unexpectedly began to drift in a southeasterly direction. In this paper, trigonometrical methods are used to derive more precise measures of the ice drift the expedition members actually experienced, based on their own position fixes and their own descriptions of their marches. The results confirm that they were exposed to a southwesterly ice drift, on average, during the weeks they were trying to head southeast, and to a southeasterly ice drift, on average, during the weeks they were trying to head southwest. Hence, the disastrous ending of the expedition was, at least to some extent, a result of bad luck.